1. Assume that f ( x ) is a one-to-one function.

a) If f(6) = 3 , then f^-1 (3) =

b) If f^−1 (−8) = −7, then f (−7)=

2.Find the inverse of f(x)= 8x + 2/5 − 7x

f^-1(x)=

3. a) f(x)=15x+24

f^-1(x)=

b) g(x)=9×3−18

g^−1(x)=

c) h(x)=15x+18

h^−1(x)=

d) j(x)=3√x+9

j^−1(x)=

4. f(x)= 7x−2 and g(x)= x+2 / 7

(a) f(g(x))=

(b) g(f(x))=

(c) Thus g (x) is called an ______ function of f (x)

5.Given f (x) = 3x + 1 , find the inverse.

f^−1(x)=

6. Given f (x) = 3/4 x + 8 , find the inverse.

f^−1(x)=

Given f (x) = 10/x+7 + 2 , find the inverse.

f^−1(x)=

1. Assume that f ( x ) is a one-to-one function. a) If f(6) = 3 , then f^-1 (3) = b) If f^−1 (−8) = −7, then f (−7)= 2.Find the inverse of f(x)= 8x + 2/5 − 7x f^-1(x)= 3. a) f(x)=15x+24 f^-1(x)=